A monarchy of letters: royal correspondence and English diplomacy in the reign of Elizabeth I - Allinson, Rayne (Queenship and power, 2012)
Tedius and paynefull : letter writing in English royal diplomacy -- My skrating hand : the making of Elizabeth's correspondence -- Entering the stage : Elizabeth's use of letters in her early reign, 1558-1559 -- War of words : King Philip II of Spain, 1558-1884 -- Silent diplomacy : Queen Mary I of Scotland, 1559-1587 -- Marriage and motherhood : Catherine de Medici, queen mother of France, 1559-1588 -- Inward and secret letters : Tsar Ivan IV of Russia, 1561-1583 -- Letters full of marvels : Sultan Murād III of the Ottoman Empire 1579-1595 -- Well worth a letter : King Henry IV of France, 1572-1603 -- Mine own hand : King James VI of Scotland, 1580-1603